Thomas' snowsuit - Munsch, Robert N., 1945-; Martchenko, Michael (Toronto : Annick Press ; New York : Distributed in the U.S.A. by Firefly Books, 1985)
His mother, teacher, and principal have a hard time trying to convince Thomas to wear his snowsuit.
3.0
K-3
K-3
AD 750
Keywords: Clothing and dress -- Fiction; Humorous stories; Clothing and dress -- Fiction; Humorous fiction